Protocol for collaboration between the national genebank and community seed banks launched and endorsed - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
Through a co-creation process with national partners in East and Southern Africa, and the Wageningen Centre for Development Innovation in the Netherlands, led by the Alliance of Bioversity International and CIAT, the protocol for collaboration between the national genebank and community seed banks was produced, disseminated through the Integrated Seed Sector Development Africa program, and endorsed by national genebanks in a number of countries.